Development and Resistance: Rural Resistance to Economic Development Practices in Western Samoa - Luther, Eudene O. (My University, 1995)
In this thesis I show that contemporary development practices in western Samoa are the product of a historical encounter between two social, political, and cultural worlds; the Samoan world characterized by a kin-ordered mode of production and the world of global capitalism. That encounter culminated in the incorporation of the Independent State of Western Samoa created and defined by members of a Samoan political elite in collaboration with members of the New Zealand colonial elite.
Since the incorporation of the Independent State of Western Samoa, successive government elites in collaboration with aid donors have attempted to implement a state-centred model of and for development directed toward the goals of national self-reliance and a condition of improved economic well-being for all Samoans. Government strategies have focused on the development of relations with patron states that provide aid in the form of grants, loans, technology, and technicians for investment, for the most part, in large state-owned commercial ventures and infrastructural projects.
Unfortunately, government strategies have failed to achieve either a movement toward national self-reliance or enhanced economic well-being for the majority of Samoans. The Government development practices have not effectively mobilized and utilized rural resources, specifically, the rural institutions of land and labour, as tools for raising productivity in the rural sector of the economy. Instead the production of export crops has stagnated or declined, and government attempts to utilize land for forestry or infrastructural projects have been met, more often than not, with resistance from people living in the rural areas. Furthermore, young Samoans continue to migrate out of the rural areas leaving their families short of labour and struggling to produce a surplus in addition to their subsistence requirements.
Keywords: Anthropology; Anthropology